Diagnosis of non-effusive feline infectious peritonitis by reverse transcriptase quantitative PCR from mesenteric lymph node fine-needle aspirates. Issue 10 (October 2019) - Dunbar, Dawn; Kwok, Wendy; Graham, Elizabeth; Armitage, Andy; Irvine, Richard; Johnston, Pamela; McDonald, Michael; Montgomery, Dorothy; Nicolson, Lesley; Robertson, Elise; Weir, William; Addie, Diane D
Objectives: The aim of this study was to evaluate a feline coronavirus (FCoV) reverse transcriptase quantitative PCR (RT-qPCR) on fine-needle aspirates (FNAs) from mesenteric lymph nodes (MLNs) collected in sterile saline for the purpose of diagnosing non-effusive feline infectious peritonitis (FIP) in cats. Methods: First, the ability of the assay to detect viral RNA in MLN FNA preparations compared with MLN biopsy preparations was assessed in matched samples from eight cats. Second, a panel of MLN FNA samples was collected from a series of cats representing non-effusive FIP cases (n = 20), FCoV-seropositive individuals (n = 8) and FCoV-seronegative individuals (n = 18). Disease status of the animals was determined using a combination of gross pathology, histopathology and/or 'FIP profile', consisting of serology, clinical pathology and clinical signs. Results: Viral RNA was detected in 18/20 non-effusive FIP cases; it was not detected in two cases that presented with neurological FIP. Samples from 18 seronegative non-FIP control cats and 7/8 samples from seropositive non-FIP control cats contained no detectable viral RNA. Thus, as a method for diagnosing non-effusive FIP, MLN FNA RT-qPCR had an overall sensitivity of 90.0% and specificity of 96.1%. Conclusions and relevance: In cases with a high index of suspicion of disease, RT-qPCR targeting FCoV in MLN FNA can provide important information to support the ante-mortem diagnosis of non-effusive FIP. Importantly, viral RNA can be reliably detected in MLN FNA samples in saline submitted via the national mail service. When applied in combination with biochemistry, haematology and serological tests in cases with a high index of suspicion of disease, the results of this assay may be used to support a diagnosis of non-effusive FIP.